Female sex offenders : an examination into university student attitudes regarding adult sexual behaviour towards children : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Aitken, Julie Lynell (Massey University, 2009)
The purpose of the present study was to examine university student attitudes regarding illegal sexual behaviour of women towards children. Attitudes toward sexual abuse are an undeveloped area of research, particularly when a woman perpetrates the abuse. Sexual offences committed by women are rare, although low estimates are speculated to be a result of the myths surrounding the sexual nature of women and the gender role prescribed for them by society. Victims are less likely to report abuse by a female, and authorities are less likely to believe victims of female perpetrated abuse. To examine whether these findings hold true within the New Zealand population, attitudes towards adult sexual behaviours were investigated, using vignettes and the attitudes regarding women's and men's sexualised behaviour towards children questionnaire. The Massey University students in the present study were found to hold different attitudes towards male and female sexual behaviour, following a similar pattern to a United Kingdom study of social workers and police officers. Female sexual behaviour was perceived as less serious and less harmful compared to male sexual behaviour. Effects on the victims of female-perpetrated abuse are discussed as well as future directions for the research of attitudes towards women who commit sexual abuse against children.
Keywords: Female sex offenders; Women child molesters; Child sexual abuse